SURVEI BEBERAPA FAKTOR RISIKO PENYAKIT TIDAK MENULAR DI KABUPATEN REMBANG (STUDI PADA SUKARELAWAN) - Putri Septyarini; Lintang Dian Saraswati; Henry Setyawan Susanto (Jurnal Kesehatan Masyarakat (Undip), 2015)
The prevalence of non-communicable disease in Rembang regency was increase 2,21% (2010), 2,40% (2011), and 2,48% (2012). The prevention of non-communicable disease should be focused on its risk factors. A cross-sectional study was conducted to obtain the major risk factors of non-communicable disease in Rembang regency. Samples were taken using the technique of multi-stage similar to a previous study in 2010. A total of 384 men aged 25-64 years stratified by place (8 coastal and 40 non-coastal region) were selected. Data risk factors of non-communicable disease were adopted by using The WHO Stepwise Approach. The result showed the majority of the respondents aged 35-44 years (43,49%), completed junior high school (33,33%), with income below the minimum wage (44,71%) and unpaid work (41,67%). The prevalence of smoking was 72,40%, hypertension 15,36%, obesity 1,56%, and overweight 18,75%. While the prevalence of hyperglycemia was 20,31%. Prevalence of non-communicable disease risk factors increased with age. Based on this research high burden of non-communicable disease risk factors in Rembang regency was increased, comparable to the previous study in Rembang regency 2010. Health promotion about healthy life style was needed to be improved as a first step to prevention.